Phylogenetic Revision of Savoryellaceae and Evidence for Its Ranking as a Subclass - Dayarathne, Monika C.; Maharachchikumbura, Sajeewa S. N.; Jones, E. B. Gareth; Dong, Wei; Devadatha, Bandarupalli; Yang, Jing; Ekanayaka, Anusha H.; De Silva, Wasana; Sarma, Vemuri V.; Al-Sadi, Abdullah M.; Khongphinitbunjong, Kitiphong; Hyde, Kevin D.; et al. (Frontiers in Microbiology, 2019)
Morpho-molecular and molecular clock analyses were conducted on Savoryellaceae in order to understand the placements of taxa in this family. Ascotaiwania and Neoascotaiwania formed a well-supported monophyletic clade in the phylogenetic analyses of concatenated partial 18S rDNA, 28S rDNA, transcription elongation factor 1-α and RNA polymerase II gene data. These two genera share similar morphological features, especially in their asexual morphs, indicating that they are congeneric. Hence, we synonymize Neoascotaiwania under Ascotaiwania. Ascotaiwania hughesii (and its asexual morph, Helicoon farinosum) and Monotosporella setosa grouped in a clade sister to Pleurotheciales and are excluded from Ascotaiwania which becomes monophyletic. A novel genus Helicoascotaiwania is introduced to accommodate Ascotaiwania hughesii and its asexual morph, Helicoon farinosum. A novel species, Savoryella yunnanensis is introduced from a freshwater habitat in Yunnan Province, China. Comprehensive descriptions and morphographs are provided for taxa in this family. In addition, we provide evolutionary divergence estimates for Savoryellomycetidae taxa and major marine based taxa to support our phylogenetic and morphological investigations. The taxonomic placement of these marine-based taxa is briefly discussed. Our results indicate that the most basal group of marine-based taxa are represented within Lulworthiales, which diverged from ancestral Sordariomycetes around 149 MYA (91–209) and Savoryellomycetidae around 213 MYA (198–303)